Sekularisasi Menurut Pandangan Harvey Cox - Permana, Dian; Mansyur, Ahmad Shalahuddin (P3TK, Sanata Dharma University, 2020)
Secularism has become a new trend in various parts of the world. Many people seem to no longer believe in the role of religion in the Society. Religion does not need to interfere with the situation that occurs in society. These problems rise different opinions and responses from various figures. Harvey Cox is one of the theologians who discusses secularization through his book entitled The Secular City. Harvey Cox argues that secularization does not need to be rejected. Secularization is a process that occurs in society, where religious affairs are separated from community affairs. Secularization is clearly different from secularism. In secularism, people see religion as a stranger and God is seen as a barrier. Through the book The Secular City, Harvey Cox offers a new perspective on secularization including how the Church should respond to secularization. This paper will also briefly mention the secularization that has occurred in Indonesia. Nurcholish Madjids thoughts equip the challenges and hopes for the Indonesian.